Factors of a physician quality improvement leadership coalition that influence physician behaviour: a mixed methods study - Pamela Mathura; Narmin Kassam; Karen Spalding; Reidar Hagtvedt; Jennifer Medves; Lenora Duhn; Sandra Marini (BMJ Open Quality)
Background A coalition (Strategic Clinical Improvement Committee), with a mandate to promote physician quality improvement (QI) involvement, identified hospital laboratory test overuse as a priority. The coalition developed and supported the spread of a multicomponent initiative about reducing repetitive laboratory testing and blood urea nitrogen (BUN) ordering across one Canadian province. This study’s purpose was to identify coalition factors enabling medicine and emergency department (ED) physicians to lead, participate and influence appropriate BUN test ordering.Methods Using sequential explanatory mixed methods, intervention components were grouped as person focused or system focused. Quantitative phase/analyses included: monthly total and average of the BUN test for six hospitals (medicine programme and two EDs) were compared pre initiative and post initiative; a cost avoidance calculation and an interrupted time series analysis were performed (participants were divided into two groups: high (>50%) and low (<50%) BUN test reduction based on these findings). Qualitative phase/analyses included: structured virtual interviews with 12 physicians/participants; a content analysis aligned to the Theoretical Domains Framework and the Behaviour Change Wheel. Quotes from participants representing high and low groups were integrated into a joint display.Results Monthly BUN test ordering was significantly reduced in 5 of 6 participating hospital medicine programmes and in both EDs (33% to 76%), resulting in monthly cost avoidance (CAN$900–CAN$7285). Physicians had similar perceptions of the coalition’s characteristics enabling their QI involvement and the factors influencing BUN test reduction.Conclusions To enable physician confidence to lead and participate, the coalition used the following: a simply designed QI initiative, partnership with a coalition physician leader and/or member; credibility and mentorship; support personnel; QI education and hands-on training; minimal physician effort; and no clinical workflow disruption. Implementing person-focused and system-focused intervention components, and communication from a trusted local physician—who shared data, physician QI initiative role/contribution and responsibility, best practices, and past project successes—were factors influencing appropriate BUN test ordering.